THE EFFECT OF BRAND AMBASSADOR AND BRAND IMAGE OF BTS TOWARD PURCHASE INTENTION (Case Study Customer of Tokopedia in Pontianak) - Andini, Ulva (Jurnal Manajemen Update, 2021)
Nowadays, the competition occurs due to the development of technology. Every e-commerce company is trying to attract potential customers by providing information about what is owned by e-commerce. The author was interested to find out the effect of strategies to face competition in maintaining market share and how to gain purchase intention of customers especially in Pontianak. Tokopedia is one brand that sees brand ambassadors which is BTS (a boy group from South Korea) as the way of promoting and implementing strategies to attract purchase intention. This research has proposed to find out how significant the influence of using Brand Ambassador and the Brand Image of BTS toward purchase intention of customers in Pontianak that using Tokopedia. The objectives of this study is to find out the effect of Brand Ambassador (which consist of: Visibility, Credibility, Attraction, Power) and Brand Image of BTS toward Purchase Intention of Tokopedia in Pontianak. This study is using questionnaires. This research was carried out among 200 respondents who are 17 and above within Pontianak City. The result of the research shows that Visibility, Credibility, Power, and Brand Image significantly influences purchase intention of Tokopedia customers in Pontianak while Attraction variable does not significantly influence purchase intention of Tokopedia customers in Pontianak. Key words: Brand Ambassador; Visibility, Credibility, Attraction, Power, Brand Image, and Purchase Intention